Coagulation Factor XIII Subunit A Is a Biomarker for Curative Effects and Prognosis in Malignant Solid Tumors, Especially Non-small Cell Lung Cancer - Luo, Yujiao; Li, Bin; Li, Ji; Zhang, Yang; Deng, Mingyang; Hu, Chunhong; Yan, Wenzhe; Zhou, Zhiguang; Zhang, Guangsen (Frontiers in Oncology, 2021)
Background: The expression of coagulant factor XIII subunit A (FXIII-A) is significantly increased in some types of cancer cells and tumor-associated macrophages (TAMs). However, few studies on plasma FXIII-A in cancer patients have been conducted and have shown contradictory results, so the relationship of plasma FXIII-A with the progression and prognosis of malignant tumors is still unknown. This study explored the association of plasma FXIII-A with a curative effect and the prognosis of patients with malignant solid tumors. Methods: We monitored plasma FXIII-A before and during systemic therapy and assessed its relationship with the curative effect and prognosis of malignant solid tumors, especially non-small cell lung carcinoma (NSCLC), by propensity-adjusted, multivariable logistic regression analysis and survival curve, in a prospective study of 1147 patients with different types of malignant solid tumors. The influencing factors of plasma FXIII-A were also analyzed. Results: We found that D-dimer (D2) = 1 mg/L was the inflection point for the association between FXIII-A and D2: FXIII-A was significantly negatively correlated with D2 (r = -0.39, p < 0.01) and FDP (r = -0.40, p < 0.01) in D2 > 1 mg/L but uncorrelated with D2 or FDP in D2 ≤ 1 mg/L, which provided a method to find a more realistic plasma FXIII-A level. Plasma FXIII-A was positively correlated with age, platelets, lymphocytes, monocytes and carcinoembryonic antigen (CEA). It was found for the first time that plasma FXIII-A was abnormally significantly increased (FXIII-A > 150%) in post-therapy patients, especially in NSCLC and lung metastasis patients, and the incidence of FXIII-A > 150% in lung adenocarcinoma was 16 times higher than that in lung squamous carcinoma. FXIII-A > 150% proved to be an independent risk factor for disease progression in NSCLC patients (OR=5.74, 95% CI: 1.20-27.60, p = 0.029), predicting poor efficacy. The marked decrease in plasma FXIII-A (FXIII-A < 40%) was related to coagulation disorders and poor prognosis with short survival time (median survival time of 4 months). Conclusions: Plasma FXIII-A has the potential to be a real-time biomarker with bidirectional indicator effects to assess curative effects and prognosis in malignant solid tumors, especially NSCLC.